The steady-state visual evoked potential in vision research: A review - Norcia, Anthony M.; Appelbaum, L. Gregory; Ales, Justin M.; Cottereau, Benoit R.; Rossion, Bruno (Journal of vision (Charlottesville, Va.), 2015)
Periodic visual stimulation and analysis of the resulting steady-state visual evoked potentials were first introduced over 80 years ago as a means to study visual sensation and perception. From the first single-channel recording of responses to modulated light to the present use of sophisticated digital displays composed of complex visual stimuli and high-density recording arrays, steady-state methods have been applied in a broad range of scientific and applied settings.The purpose of this article is to describe the fundamental stimulation paradigms for steady-state visual evoked potentials and to illustrate these principles through research findings across a range of applications in vision science.